2016
DOI: 10.1016/j.trecan.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

SASP: Tumor Suppressor or Promoter? Yes!

Abstract: Cellular senescence is a permanent growth arrest in cells with damage or stress that could lead to transformation. Some tumor cells also undergo senescence in response to chemotherapy. Senescent cells secrete cytokines and other factors of the senescence-associated secretory phenotype (SASP) that contribute to tumor suppression by enforcing arrest and recruiting immune cells that remove these damaged or oncogene-expressing cells from organisms. However, some cells can develop a SASP comprising factors that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
151
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(153 citation statements)
references
References 105 publications
(130 reference statements)
2
151
0
Order By: Relevance
“…Further research using human patient samples and mouse models has demonstrated that p53 wild-type breast tumors respond to chemotherapy by entering cell cycle arrest and senescence with concomitant expression of cytokines and chemokines of the senescence-associated secretory phenotype (SASP; te Poele et al, 2002; Jackson et al, 2012; Tonnessen-Murray et al, 2018). The SASP can promote tumorigenic properties such as proliferation, survival, stemness, immune evasion, and metastasis (Rodier et al, 2009; Achuthan et al, 2011; Cahu et al, 2012; Canino et al, 2012; Toso et al, 2014; Rao and Jackson, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Further research using human patient samples and mouse models has demonstrated that p53 wild-type breast tumors respond to chemotherapy by entering cell cycle arrest and senescence with concomitant expression of cytokines and chemokines of the senescence-associated secretory phenotype (SASP; te Poele et al, 2002; Jackson et al, 2012; Tonnessen-Murray et al, 2018). The SASP can promote tumorigenic properties such as proliferation, survival, stemness, immune evasion, and metastasis (Rodier et al, 2009; Achuthan et al, 2011; Cahu et al, 2012; Canino et al, 2012; Toso et al, 2014; Rao and Jackson, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We also demonstrated the susceptibility of cygb ‐knockout mice to develop liver cancer when treated with diethylnitrosamine or a choline‐deficient L‐amino acid‐defined diet, implicating the regulatory role of CYGB in HSCs for the development of the tumor microenvironment . In addition, senescent HSCs showing the senescence‐associated secretory phenotype (SASP) produce a variety of secreted proteins, such as cytokines, chemokines, and proteases, that promote liver tumor progression and are present in an obesity‐associated liver tumor microenvironment (Fig. ).…”
Section: Hscs and Their Roles In Fibrosis And Liver Cancermentioning
confidence: 83%
“…These factors have been reported to be important components of SASP. 33 IL-6 is a pleiotropic factor, which elicits a wide spectrum of physiological and pathogenic events such as cell proliferation. 34 Indeed, IL-6 promoted the proliferation of serum-depleted MCF-10A cells in a dose-dependent manner, while neutralization of IL-6 by specific antibody abrogated this effect (Fig.…”
Section: Il-6 Secreted By Senescent Cells Stimulated Cell Proliferationmentioning
confidence: 99%